Crystal structures of U6 snRNA-specific terminal uridylyltransferase - Seisuke Yamashita (Nature Portfolio, 2017)
After transcription the 3′-end of U6 snRNA is oligo-uridylylated by the terminal uridylyltransferase TUT1. Here the authors present the crystal structure of human TUT1 and give insights into the mechanism of 3′-end uridylylation by the enzyme.